2016
DOI: 10.17795/nmsjournal31292
|View full text |Cite
|
Sign up to set email alerts
|

Support in Clinical Settings as Perceived by Nursing Students in Iran: A Qualitative Study

Abstract: BackgroundAlthough support is one of the most substantial needs of nursing students during clinical education, it is not clearly defined in the literature.ObjectivesThe current study aimed to explore the concept of support in clinical settings as perceived by nursing students.Materials and MethodsA qualitative content analysis was used to explore the meaning of student support in clinical settings. A purposive sampling with maximum variation was used to select the participants among bachelor nursing students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…In the current study, being receiving feedback gives selfconfidence, and patient family cooperation helps me to be more confident are considered of the common facilitating factors in clinical setting practice. This study is congruent with Joolaee et al, (2016) [33] who reported that the students frequently mentioned that they felt confident when receiving appropriate support from their instructors and other sources of support in the ward. Also, Al sharani, (2015) [34] reported that one of the factors facilitating clinical placement is feedback from clinical lectures.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, being receiving feedback gives selfconfidence, and patient family cooperation helps me to be more confident are considered of the common facilitating factors in clinical setting practice. This study is congruent with Joolaee et al, (2016) [33] who reported that the students frequently mentioned that they felt confident when receiving appropriate support from their instructors and other sources of support in the ward. Also, Al sharani, (2015) [34] reported that one of the factors facilitating clinical placement is feedback from clinical lectures.…”
Section: Discussionsupporting
confidence: 90%
“…(1) The quality of nursing care depends on the quality education in the clinical setting, and the qualitative clinical education is provided, the more successful and professional students will graduate, which can result in a healthier community. (1,5) Training includes various components such as students, instructors, resources and facilities, hospital staff, educational materials, and clinical settings. To understand the status of education, one can use the views of stakeholders and experts.…”
mentioning
confidence: 99%
“…Students' experiences in this environment will lead to a better understanding of the conditions prevailing at the clinical environment and thus a better understanding of the factors affecting clinical education. (5,6) Many factors, such as the quality of instructors' education, the quality of the monitoring of the student learning process, the educational facilities and the psychological environment affecting the clinical environment, affect education of nursing students in clinical setting. (4) Identifying the problems and challenges of clinical education and timely correction facilitate the training process and improve the quality.…”
mentioning
confidence: 99%
“…The results of the study by Choi, et al [12] said that the factors that influence student nurses' anxiety before entering the clinic are ICHT 2019 pleasure in the subject, their satisfaction when practicing in class, guidance on how to deal with anxiety. Different research conducted in Iran by Joolaee et al [13] say that humanistic behavior such as appreciative communication, acceptance of students in clinics, increasing student confidence, accepting professions truly being the support of student practice. Under these conditions students are not focused on fear that causes anxiety in practice that affects the acquisition of grades.…”
Section: Discussionmentioning
confidence: 99%